Analisis Faktor-Faktor yang Mempengaruhi Tingkat Partisipasi Angkatan Kerja di Indonesia Tahun 2001-2020 - Rena Armita Sari; Rr Retno Sugiharti (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
LFPR is an important factor that can show how large the workforce is already working. The large number of workers who do not work causes the burden of dependence to be greater. In this study, it is shown that LFPR is influenced by growth in the number of MSMEs, household consumption, and minimum wages. In data processing, an ECM (error correction model) approach is used which looks at its long-term and short-term effects. In the long term and in the short term, the growth in the number of MSMEs and the minimum wage has a significant negative effect, while household consumption has a significant positive effect simultaneously or partially, except for the minimum wage variable in the short term which has an insignificant negative effect.